Influence of Surface Properties on the Adhesion of Staphylococcus epidermidis to Acrylic and Silicone - Sousa, Cláudia; Teixeira, Pilar; Oliveira, Rosário (International Journal of Biomaterials, 2009)
The aim of the present study was to compare the ability of eight Staphylococcus epidermidis strains to adhere to acrylic and silicone, two polymers normally used in medical devices manufacture. Furthermore, it was tried to correlate that with the surface properties of substrata and cells. Therefore, hydrophobicity and surface tension components were calculated through contact angle measurements. Surface roughness of substrata was also assessed by atomic force microscopy (AFM). No relationship was found between microbial surface hydrophobicity and adhesion capability. Nevertheless, Staphylococcus epidermidis IE214 showed very unique adhesion behaviour, with cells highly aggregated between them, which is a consequence of their specific surface features. All strains, determined as being hydrophilic, adhered at a higher extent to silicone than to acrylic, most likely due to its more hydrophobic character and higher roughness. This demonstrates the importance of biomaterial surface characteristics for bacterial adhesion.